2015
DOI: 10.1107/s1399004715002308
|View full text |Cite
|
Sign up to set email alerts
|

Capture and X-ray diffraction studies of protein microcrystals in a microfluidic trap array

Abstract: A microfluidic platform has been developed for the capture and X-ray analysis of protein microcrystals, affording a means to improve the efficiency of XFEL and synchrotron experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 65 publications
0
72
0
Order By: Relevance
“…A fixed target method is now capable of delivering crystals at the repetition rates of the existing XFEL sources [50] . Microfluidic flow cells would be useful for precious protein samples [51,52] . Sample injection with a coaxial sheath liquid can help to suppress a sample amount even in the case of continuous-flow liquid jet [34] .…”
Section: Discussionmentioning
confidence: 99%
“…A fixed target method is now capable of delivering crystals at the repetition rates of the existing XFEL sources [50] . Microfluidic flow cells would be useful for precious protein samples [51,52] . Sample injection with a coaxial sheath liquid can help to suppress a sample amount even in the case of continuous-flow liquid jet [34] .…”
Section: Discussionmentioning
confidence: 99%
“…25,31,33,34,37,143,185,[191][192][193][194][195] The simplest mounting strategy involves the deposition of a crystal slurry between two thin silicon nitride wafers. 143 However, most approaches have utilized microfabricated mesh-type structures.…”
Section: Sample Arraysmentioning
confidence: 99%
“…Brunger et al reported a microfluidic trap array which utilized hydrodynamic forces to arrange microcrystals grown off-chip into an ordered array ( Figure 9). 33 In contrast, Fraden et al reported that kinetic optimization of droplet-microfluidics was used to ensure the growth of only a single in each droplet. 15 The droplets were then arranged into a microfluidic array for subsequent analysis (Figure 8(b)).…”
Section: Sample Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Such platforms have been increasingly harnessed to facilitate the diffraction analysis of challenging targets for both static and dynamic structure determination. Various platforms have been developed to improve the growth and subsequent mounting of tiny and fragile crystals for X-ray diffraction analysis [24][25][26][27][28], including dense array-style devices [29][30][31][32][33][34][35][36][37][38][39][40][41], platforms for the lipidic cubic phase crystallization of membrane proteins [42,43], and thin-film sandwich devices [44]. In the meantime, the challenges of such platforms lie in the need to maintain a protected sample environment, as well as minimize the interference of device materials with the subsequent X-ray analysis.…”
Section: Introductionmentioning
confidence: 99%